Brazilian Mangroves: Blue Carbon Hotspots of National and Global Relevance to Natural Climate Solutions - Rovai, Andre S.; Twilley, Robert R.; Worthington, Thomas A.; Riul, Pablo (Frontiers in Forests and Global Change, 2022)
Mangroves are known for large carbon stocks and high sequestration rates in biomass and soils, making these intertidal wetlands a cost-effective strategy to some nations to compensate for a portion of their carbon dioxide (CO2) emissions. However, few countries have the national-level inventories required to support the inclusion of mangroves into national carbon credit markets. This is the case for Brazil, home of the second largest mangrove area in the world but lacking an integrated mangrove carbon inventory that captures the diversity of coastline types and climatic zones in which mangroves are present. Here we reviewed published datasets to derive the first integrated assessment of carbon stocks, carbon sequestration rates and potential CO2eq emissions across Brazilian mangroves. We found that Brazilian mangroves hold 8.5% of the global mangrove carbon stocks (biomass and soils combined). When compared to other Brazilian vegetated biomes, mangroves store up to 4.3 times more carbon in the top meter of soil and they are second in biomass carbon stocks only to the Amazon forest. Moreover, organic carbon sequestration rates in Brazilian mangroves soils are 15-30% higher than recent global estimates; and integrated over the country’s area, they account for 13.5% of the carbon buried in world’s mangroves annually. Carbon sequestration in Brazilian mangroves woody biomass is 10% of carbon accumulation in mangrove woody biomass globally. Our study identifies Brazilian mangroves as a major global blue carbon hotspot as well as suggesting that their loss could potentially release substantial amounts of CO2. This research provides a robust baseline for the consideration of mangroves into strategies to meet Brazil’s intended Nationally Determined Contributions.